ECONOMIC SANCTIONS IN THE COMPETITION - M. Fomicheva (Вестник университета, 2016)
The article presents a retrospective of the history of economic sanctions and their application in the XX - XXI century. Approaches to the definition of the concepts of sanctions and economic sanctions. Conditionally allocated types of sanctions. Analyzes the political and economic objectives of the sanctions. Identified measures pressure of rating agencies. Estimated losses from the imposition of sanctions for the initiating country.